Technology implementation barriers in the Malaysian herbal industry: A case study in northern Malaysia - Nordin, Norani; Othman, Siti Norezam; Che Mat, Ruzinoor (2005)
Technology is an essential component in all types of organisations and most organisations have reasons to implement new technology.The most fundamental justification for new technology implementation is that the technology must be able to contribute to strong competitive advantages and also increase or create long-term profit.In most small and medium enterprises (SMEs), there are barriers or obstacles in implementing these technologies.This paper the qualitative study aimed in investigating barriers faced by the Malaysian herbal industry in implementing technologies in their factory.Most of the local herbal manufacturing firms are categorised as SMEs which are usually considered to be lagged behind larger companies in technology usage. As this was an exploratory research, a case study method is used as it gave us the in dept exploration in order to develop and understand the importance of the identified variables our qualitative results suggest that the main constraints in implementing technologies are lack of technical specialist and capital and also internal managerial problem